Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fpsyg.2017.00031
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Therapy for Depression in Adults: A Waiting List Randomized Controlled Trial with Six Months Follow-Up

Abstract: This randomized controlled trial examines the efficacy of metacognitive therapy (MCT) for depression. Thirty-nine patients with depression were randomly assigned to immediate MCT (10 sessions) or a 10-week wait list period (WL). The WL-group received 10 sessions of MCT after the waiting period. Two participants dropped out from WL and none dropped out of immediate MCT treatment. Participants receiving MCT improved significantly more than the WL group. Large controlled effect sizes were observed for both depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 38 publications
(50 reference statements)
2
45
0
Order By: Relevance
“…Three studies compared a total sample of 99 patients with depression (Hagen et al, ; Mami, Sharifi, & Mahdavi, ; Zemestani, Davoodi, Honarmand, Zargar, & Ottaviani, ) receiving MCTherap with patients on a waitlist to receive MCTherap. Overall, MCTherap was superior in alleviating depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies compared a total sample of 99 patients with depression (Hagen et al, ; Mami, Sharifi, & Mahdavi, ; Zemestani, Davoodi, Honarmand, Zargar, & Ottaviani, ) receiving MCTherap with patients on a waitlist to receive MCTherap. Overall, MCTherap was superior in alleviating depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…The WL group received 10 sessions of MCT after the waiting period. Results showed that 70-80% were recovered at post-treatment and 6-month follow-up (Hagen et al, 2017). The treatment was also associated with large reductions in interpersonal problems, even though MCT does not directly target such problems (Strand et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Rumination seems to exacerbate negative mood and could trigger and prolong depression (e.g., Nolen-Hoeksema et al, 2008). MCT could therefore be beneficial for people with depression as suggested by several treatment studies with recovery rates ranging around 70-80% (e.g., Wells et al, 2009Wells et al, , 2012Dammen et al, 2016;Hagen et al, 2017;Normann and Morina, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a comparatively new form of treatment, the evidence base for metacognitive therapy (MCT) is growing. Large treatment effects have been found for MCT in individual as well as group treatment of generalized anxiety disorder (GAD; McEvoy, Erceg‐Hurn, Anderson, Campbell, Swan, et al, ; van der Heiden, Muris, & van der Molen, ), depression (Dammen, Papageorgiou, & Wells, ; Hagen et al, ), and obsessive‐compulsive disorder (OCD; Rees & van Koesveld, ). Large within‐group effect sizes were reported in a recent meta‐analysis of 16 published and unpublished studies of MCT for anxiety and depression (Normann, van Emmerik, & Morina, ).…”
Section: Introductionmentioning
confidence: 99%